Growth rate of coeliac children is compromised before the onset of the disease. Issue 10 (30th April 2020) - Auricchio, Renata; Stellato, Pio; Bruzzese, Dario; Cielo, Donatella; Chiurazzi, Alfredo; Galatola, Martina; Castilljeo, Gemma; Crespo Escobar, Paula; Gyimesi, Judith; Hartman, Corina; Kolacek, Sanja; Koletzko, Sybille; et al.
Abstract : Introduction: Growth impairment has often been described in children who develop coeliac disease (CD). Based on data from the multicentre, longitudinal PreventCD study, we analysed the growth patterns of infants at genetic risk of CD, comparing those who developed CD by 6 years of age (CD 'cases', 113 infants) versus those who did not develop CD by 6 years (no CD 'controls', 831 infants). Methods: Weight and length/height were measured using a longitudinal protocol. Raw measurements were standardised, computing z-scores for length/height and weight; a linear mixed model was fitted to the data in order to compare the rate of growth in the two cohorts. Results: Neither cases nor controls had significant growth failure. However, when the mean z-scores for weight and height were analysed, there was a difference between the two groups starting at fourth month of life. When the growth pattern in the first year was analysed longitudinally using mixed models, it emerged that children who develop CD had a significantly lower growth rate in weight z-score (−0.028/month; 95% CI −0.038 to −0.017; p<0.001) and in length/height z-score (−0.018/month; 95% CI −0.031 to −0.005; p=0.008) than those who do not develop CD. When the whole follow-up period was analysed (0–6 years), differences between groups in both weight and length/height z-scores were confirmed. Conclusion: The growth of children at risk of CD rarely fell below 'clinical standards'. However, growth rate was significantly lower in cases than in controls. Our data suggest that peculiar pathways of growth are present in children who develop CD, long before any clinical or serological signs of the disease appear.